STUDY ON DETERMINING THE LOCATION FOR THE DEVELOPMENT OF A TYPE A PASSENGER TERMINAL IN TANJUNG SELOR, NORTH KALIMANTAN PROVINCE - Muhammad Rafly Alief Rizqy Hariyono; Alfa Narendra (RADJA PUBLIKA, 2026)
This study aims to identify the development potential of the Tanjung Selor Type A Terminal through the mixed use development approach, which integrates transportation, commercial, and social functions. The research focuses on assessing the feasibility of the terminal from technical, economic, social, and spatial aspects, as well as formulating development strategies that are adaptive to local characteristics. The research employed a mixed method approach, combining qualitative and quantitative techniques. Primary data were collected through questionnaires, interviews, and field observations, while secondary data were obtained from spatial planning documents, demographic statistics, and transportation records. The analysis consisted of spatial assessment, SWOT analysis, and trip generation–attraction forecasting to project future travel demand. The findings indicate that the Tanjung Selor Type A Terminal has significant potential to be developed as a multifunctional hub. Strength factors include strategic location in accordance with the regional spatial plan, high accessibility, and alignment with the New Independent City development agenda. Opportunities lie in integrating local economic activities through MSMEs, trade, and public spaces. The proposed development strategy emphasizes functional zoning, multimodal integration, and a mixed use development concept that enhances connectivity, stimulates local economic growth, and creates inclusive public spaces.